Navigating the Post-Pandemic Workplace: A Study of Remote Work Management and Employee Well-being - Phukan, Ranjeeta (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
The worldwide COVID-19 pandemic has redefined the way we work, accelerating the transition from conventional office-based work to remote and hybrid work. This research aims to compare employees’ perceptions and behaviours towards post-pandemic remote work vs office work. Based on a quantitative research design, data were collected using structured questionnaires with 100 respondents from different sectors. The research seeks to explore the key drivers of employee productivity, collaboration, job satisfaction, and work-life balance, and the relevance of technology and organizational support in this context. Regression analysis was used to unpack associations, and the incremental views offered evidence of nuanced variation in employee engagement and well-being by work modality. The results are designed to help organisations develop flexible workplace policies that will ensure and improve productivity, job satisfaction and general health in the changing post-pandemic workplace.